Rancang Bangun Aplikasi E-Learning Berbasis Progressive Web Apps Untuk Menunjang Pembelajaran Online dengan Metode Prototyping - Hardianty, Dini Agnia; Yustiana, Indra; Somantri, S (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Covid-19 pandemic has an impact on the Indonesian education system which makes the learning process from offline to online. This is what prompted Hayyatan Thayyibah High School to create an E-Learning application to support the online learning process, apart from being used for online learning, the Hayyatan Thayyibah High School E-learning application was also used to share information and take attendance for reading the Qur'an (Tallaqi). The E-Learning application was built using the Prototyping method, from the results of usability testing, an average score of 80% showed that the application could be used well by students and the teacher.